Lung Recruitment, Individualized PEEP, and Prone Position Ventilation for COVID-19-Associated Severe ARDS: A Single Center Observational Study - Sang, Ling; Zheng, Xia; Zhao, Zhanqi; Zhong, Min; Jiang, Li; Huang, Yongbo; Liu, Xiaoqing; Li, Yimin; Zhang, Dingyu (Frontiers in Medicine, 2021)
Background: Patients with coronavirus disease 2019 (COVID-19) may develop severe acute respiratory distress syndrome (ARDS). The aim of the study was to explore the lung recruitability, individualized positive end-expiratory pressure (PEEP) and prone position in COVID-19 associated severe ARDS. Methods: Twenty patients who met the inclusion criteria were studied retrospectively (average value of PaO2/FiO2 was 68 mmHg). The patients were ventilated under volume-controlled mode with tidal volume of 6 mL/kg predicted body weight. The lung recruitability was assessed via the improvement of PaO2, PaCO2 and static respiratory system compliance (Cstat) from low to high PEEP (5-15 cmH2O). Patients were considered recruitable if two out of three parameters improved. Subsequently, PEEP was titrated according to the best Cstat. The patients were turned to prone position for further 18-20 hours. Results: For recruitability assessment, average value of PaO2 was slightly improved at PEEP 15 cmH2O (68.0±10.3 vs. 69.7±7.9 mmHg, baseline vs. PEEP 15 cmH2O; p=0.31). However, both PaCO2 and Cstat worsened (PaCO2: 72.5±7.1 vs. 75.1±9.0 mmHg; p<0.01. Cstat: 17.5±3.5 vs. 16.6±3.9 ml/cmH2O; p=0.05). Only four patients (20%) were considered lung recruitable. Individually titrated PEEP was higher than the baseline PEEP (8.0±2.1 cmH2O, p<0.001). After 18-20 hours prone positioning, investigated parameters were significantly improved compared to the baseline (PaO2: 82.4±15.5 mmHg. PaCO2: 67.2±6.4 mmHg. Cstat: 20.6±4.4 ml/cmH2O. All p<0.001 vs. baseline). Conclusions: Lung recruitability was very low in COVID-19 associated severe ARDS. Individually titrated PEEP and prone positioning might improve lung mechanics and blood gasses.